EORS: development of online event reservation system for Olivarez College Parañaque - Duran, Marc Gil; Hideki, Castillon; Geraga, Rafael; Salcedo, Vincent; Velasquez, Derick (Para{dblac}aque CIty: Olivarez College, 2021)
The present health issue in the Philippines has pushed most of the people to become more reliant on technology. With this, schools and colleges are formulating new policies in order to prepare for the re-opening of face-to-face classes. The researchers' preferred programming languages were JavaScript, HTML, mySQL, and PHP Web Developer 2010. The proposed system served as a tool for Olivarians to become acquainted with the school hall reservation system. This study's data came from students, teachers, and non-teaching personnel at Olivarez College in Paranaque City. For this study, the researchers must properly evaluate the findings from the conducted surveys, as the outcomes of the data collection approach should serve as the foundation for creating their system. The researchers used a questionnaire divided into six categories: function stability, performance efficiency, portability, usability, reliability, and security. The questions with 5-point Likert scale was used to assess the system's quality characteristics. As a result of the system's pilot testing, majority of the users have strongly agreed to the system's functionality, efficiency, usability, security, as well as portability. The Event Online Reservation System, on the other hand, has limitations as a system. According to the statistician's findings from the data acquired, the unique feature of the suggested method suggests a high level of reliability, and the majority of respondents offer the highest grade, indicating that they strongly agree. The system's quality meets the stated and implied needs of its various stakeholders, which categorizes product quality into characteristics, the first category functional suitability represents the degree to which a product or system provides functions that meet stated and implied needs when used under specified conditions.
Undergraduate Thesis
Keywords: Online directories; Event management; Technology